Mitochondrial genome variation and intergenomic sequence transfers in Hevea species - Niu, Yingfeng; Gao, Chengwen; Liu, Jin (Frontiers in Plant Science, 2024)
Among the Hevea species, rubber tree (Hevea brasiliensis) is the most important source of natural rubber. In previous studies, we sequenced the complete nuclear and chloroplast genomes of Hevea species, providing an invaluable resource for studying their phylogeny, disease resistance, and breeding. However, given that plant mitochondrial genomes are more complex and more difficult to assemble than that of the other organelles, little is known about their mitochondrial genome, which limits the comprehensive understanding of Hevea genomic evolution. In this study, we sequenced and assembled the mitochondrial genomes of four Hevea species. The four mitochondrial genomes had consistent GC contents, codon usages and AT skews.However, there were significant differences in the genome lengths and sequence repeats. Specifically, the circular mitochondrial genomes of the four Hevea species ranged from 935,732 to 1,402,206 bp, with 34-35 unique protein-coding genes, 35-38 tRNA genes, and 6-13 rRNA genes. In addition, there were 17,294-46,552 bp intergenomic transfer fragments between the chloroplast and mitochondrial genomes, consisting of eight intact genes (psaA, rrn16S, rrn5S, rrn4.5S,, intergenic spacer regions and partial gene sequences. The evolutionary position of Hevea species, crucial for understanding its adaptive strategies and relation to other species, was verified by phylogenetic analysis based on the protein-coding genes in the mitochondrial genomes of 21 Malpighiales species.The findings from this study not only provide valuable insights into the structure and evolution of the Hevea mitochondrial genome but also lay the foundation for further molecular, evolutionary studies, and genomic breeding studies on rubber tree and other Hevea species, thereby potentially informing conservation and utilization strategies.